Molecular dynamics simulations of alanine rich β-sheet oligomers: Insight into amyloid formation - Ma, Buyong (Cold Spring Harbor Laboratory Press, 2002)
The aggregation observed in protein conformational diseases is the outcome of significant new β-sheet structure not present in the native state. Peptide model systems have been useful in studies of fibril aggregate formation. Experimentally, it was found that a short peptide AGAAAAGA is one of the most highly amyloidogenic peptides. This peptide corresponds to the Syrian hamster prion protein (ShPrP) residues 113–120. The peptide was observed to be conserved in all species for which the PrP sequence has been determined. We have simulated the stabilities of oligomeric AGAAAAGA and AAAAAAAA (A8) by molecular dynamic simulations. Oligomers of both AGAAAAGA and AAAAAAAA were found to be stable when the size is 6 to 8 (hexamer to octamer). Subsequent simulation of an additional α-helical AAAAAAAA placed on the A8-octamer surface has revealed molecular events related to conformational change and oligomer growth. Our study addresses both the minimal oligomeric size of an aggregate seed and the mechanism of seed growth. Our simulations of the prion-derived 8-residue amyloidogenic peptide and its variant have indicated that an octamer is stable enough to be a seed and that the driving force for stabilization is the hydrophobic effect.